Evaluation of performance at experimental buildings and real demonstration sites in BFIRST project: Theoretical and practical aspects for BIPV monitoring system - Pellegrino, Michele; Matano, Arturo; Flaminio, Giovanni; Sanz, A.; Roman, Eduardo; Pierret, Stéphane; Kyritsis, Anastasios; Nikoletatos, John; Tselepis, Stathis; Mathas, E.; Kalogirou, Soteris A. (My University, 2017)
Monitoring is one of the main activity of BFIRST, Building-integrated FIbre-Reinforced Solar Technology, project, a 5 years funded European project, project reference number 29601, that started in April 2102 and deals with the design, development and demonstration of a portfolio of innovative photovoltaic products for building integration, based on cell encapsulation within fibre-reinforced composite materials. Automatic data acquisition systems are generally required for monitoring, performance evaluation and exchanging data of PV systems. Standard IEC 61724:1998 “Photovoltaic system performance monitoring –Guidelines for measurement, data exchange and analysis” provides a guideline that shall be followed in these cases. As far as Building Integrated Photovoltaics (BIPV) are considered, besides electrical parameters there is in addition the need to monitor the specific building performances. That is because a BIPV module operates as a multi-functional building construction material; it generates energy and serves as part of the building envelope. Since the building related performances are not included in the aforementioned IEC standard, a general guideline for monitoring was prepared within the project that has been used within the project at two levels: one at experimental sites mainly related to experimental single module testing and the other at demosite with real PV size plants.
Keywords: Photovoltaic system performance monitoring; Building Integrated Photovoltaics